Redução da moral à estética - arte e gaia ciência na filosofia do espírito livre, de Friedrich Nietzsche - Silva, Leonardo Camargo Da [UNIFESP] (2020)
This master’s dissertation, main topic, deals with the further development of Nietzsche’s philosophy of the free spirit shown in his work Gay Science. Sources and texts are analyzed, from a genetic-conceptual perspective, to rebuild the core of his philosophical intention and argumentative path of thinking. Placing art at the center of his philosophical project is the general thesis’s basis which develops a deeply affirmative philosophical way of life, simultaneously, as an authentic artistic perspective of existence and also the overcoming of morals. In order to demonstrate it, the text will be focused on two aspects: (i) rebuilding the semantic content of the notion of gay science from Nietzsche’s texts and other authors and their incorporation and strategies uses in the text of Zarathustra’s author of showing his intrinsic relation with the artistic activity; (ii) analyzing the theme God’s death as a world’s interpretation by discussing the disruptive power of art by the overcoming of morals; finally shaping the task of the free spirit supported by art. Thus, the dissertation proposes itself a body text interpretation of Nietzsche’s Gay Science under the aspects of the problems permeating the philosophy for free spirits.